2013
DOI: 10.1007/s00276-013-1146-9
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral persistent sciatic vein: report of a case with developmental, histological and clinical aspects

Abstract: In accordance with the findings, the variant vein was concluded to be an embryonic remnant, rather than an acquired one subsequent to any obstruction of the femoral vein. Regarding their connection with the popliteal vein but not with the internal iliac vein, both variant veins were denominated as "lower type persistent sciatic vein". Such a variation would be important with respect to the risk of complication during popliteal sciatic nerve blockade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Ours were 8.6 and 9.6 mm, respectively. The PSVs in both case reports drained into the deep femoral vein (10). In our case, there was not an accompanying artery at the back of the thigh and the variant vein had no communication with the inferior gluteal vein or perforating veins along its course.…”
Section: Discussionmentioning
confidence: 44%
“…Ours were 8.6 and 9.6 mm, respectively. The PSVs in both case reports drained into the deep femoral vein (10). In our case, there was not an accompanying artery at the back of the thigh and the variant vein had no communication with the inferior gluteal vein or perforating veins along its course.…”
Section: Discussionmentioning
confidence: 44%
“…The prevalence of PSV is even higher in individuals with the KTWS. [4,11,12] For instance, Cherry et al, [5] found a PSV in 20 (48%) out of 41 KTWS patients who were diagnosed through magnetic resonance imaging (MRI). A similar study on KTWS by Noel et al, [12] found a PSV prevalence of 20%.…”
Section: Discussionmentioning
confidence: 99%
“…PSV can be present unilaterally [5,[13][14][15] or bilaterally, [5,7,11,12] and can occur as a single large vein [4,12] or a network of veins. [4,5] It can also present concurrently with a persistent sciatic artery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations